SEJARAH DAN PROGRAM PENDIDIKAN MA’HAD AL-BIRR PADA UNIVERSITAS MUHAMMADIYAH MAKASSAR - ., Muzizatullah; Yaumi, Muhammad; Getteng, Abdurrahman (Inspiratif Pendidikan, 2018)
This article aimed at describing the history of Ma'had Al-Birr at the University of Muhammadiyah Makassar and explaining the educational programs developed in accordance with the demands of the times. Data collection methods were in-depth interview, observation, and document study relating to Ma'had Al-Birr. Data Analysis was carried out by following the Miles, Huberman, and Saldana model, namely data condensation, data display, verification and conclusion drawing. In order to have accurate data, the researchers conducted internal, external, dependability and objectivity validity. The results showed that since its establishment in 1996, Ma'had Al-Birr of UNISMUH Makassar developed according to the needs of the community. The establishment was based on the collaboration between UNISMUH and the Dār al-Birr foundation that changed its name became the Asian Muslim Foundation in 2002. Ma'had Al-Birr of UNISMUH carried out the Arabic education program (I'dad Lughawy), tahfidz Al-Qur'an, Da'wah, and Shari 'ah.